Modelo de desarrollo y élites económicas en Bolivia: análisis de la concepción del desarrollo ancestral del presidente Evo Morales (2015)
Currently the Plurinational State of Bolivia faces a conflict determined by the tension between two antagonistic conceptions of economic development: President Evo Morales's conception based in the mixture of the ancestral indigenous conception of the world on the one hand and the socialist economic model on the other, and the capitalist conception led by the regional government of Santa Cruz de la Sierra, supported by the transnational companies and the country's traditional elites. This article analyzes the relationship between the concept of development of the indigenous president and the socialist model, and the incidence of the elites of Santa Cruz de la Sierra in the implementation of President's Morales model taking into account the control they have of the productive apparatus.